Information and communications technology integration in higher education curriculum - Molano, Renato Jose Ma. V. (Animo Repository, 2007)
The Integration of Information Technology in Education is becoming an important and crucial trend in the 21st century academic pursuits. It is the goal of this paper to be able to show its relevance in every school's endeavor as well as to give a clear perspective of the what's, how's and why's of pursuing technology integration in all modern-day curriculum, particularly in the tertiary education or graduate programs. This paper will give focus on the College of Computer Studies (CCS) of De La Salle University - Manila (DLSU) where the proponent is associated with, but any school for that matter can benefit from this paper, since the experiences and insights gained are universal in application. Technology Integration in Education is no easy task. As in any major project or endeavor, Technology Planning is fundamental to its success. Though it looks simple from a macro perspective, it involves more than just purchasing Information and Communications Technologies (ICTs), giving training to people concerned, and implementing it. This paper reveals a lot about its complexities, especially in the consequences Educational Technology entails. Hopefully, this will guide other academic institutions to further enhance their strategies in ensuring 100% integration of technology in their educational curriculum.